2020
DOI: 10.3390/molecules25112470
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Organic Matter on Polycyclic Aromatic Hydrocarbon (PAH) Availability and Persistence in Soils

Abstract: Polycyclic aromatic hydrocarbons (PAHs) exhibit persistence in soils, and most of them are potentially mutagenic/carcinogenic and teratogenic for human beings but also influence the growth and development of soil organisms. The PAHs emitted into the atmosphere are ultimately deposited (by dry or wet deposition processes) onto the soil surface where they tend to accumulate. Soil organic matter (SOM) plays an important role in the fate and transformation processes of PAHs, affecting their mobility, availability,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 40 publications
2
15
0
Order By: Relevance
“…While pesticides are sprayed directly at plants and soil, only about 1% of the sprayed pesticide reaches the target [ 59 ]. Pesticides accumulate in the environment, polluting its water and soil, and having a negative impact on its inhabitants [ 60 , 61 , 62 ]. In this regard, it is extremely important to search for environmentally benign substances to improve the state of the environment and of cultivated plants.…”
Section: Resultsmentioning
confidence: 99%
“…While pesticides are sprayed directly at plants and soil, only about 1% of the sprayed pesticide reaches the target [ 59 ]. Pesticides accumulate in the environment, polluting its water and soil, and having a negative impact on its inhabitants [ 60 , 61 , 62 ]. In this regard, it is extremely important to search for environmentally benign substances to improve the state of the environment and of cultivated plants.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the main sources of PAHs came from the coal and wood combustion. The origin of PAHs in the soil is connected to the decomposition of airborne particles that were emitted from natural as well as anthropogenic sources [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Soil is a porous and complex mixture, containing inorganic elements and compounds formed and anthropogenic pollutants [ 33 ]. Numerous factors can influence the rate and extent of PAH biodegradation in soil [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ], including organic matter content, nutrient content, fertilization, C:N:P ratio, microbial counts, electron acceptors, temperature, moisture, pH, and oxygen concentration. PAHs are removed from soil both with [ 42 ] and without microbial involvement [ 43 ].…”
Section: Discussionmentioning
confidence: 99%